Dinutuximab beta combined with chemotherapy in patients with relapsed or refractory neuroblastoma - Wieczorek, Aleksandra; Zaniewska-Tekieli, Anna; Ehlert, Karoline; Pawinska-Wasikowska, Katarzyna; Balwierz, Walentyna; Lode, Holger (Frontiers in Oncology, 2023)
Prognosis in children with refractory and relapsed high-risk neuroblastoma is poor. Only a minority of patients obtain remission when treated with second-line chemotherapy regimens. Chemotherapy combined with anti-GD2 antibodies has previously been shown to increase response and survival rates. We retrospectively analyzed a cohort of 25 patients with relapsed or refractory high-risk neuroblastoma who were treated with irinotecan/temozolomide chemotherapy in combination with the anti-GD2 antibody dinutuximab beta. The therapy resulted in an objective response rate of 64%, with 32% of patients achieving a complete response. Response to treatment was observed in patients with refractory disease (n=5) and those with first (n=12) or consecutive (n=8) relapses, including patients with progressing disease. In four patients, best response was achieved after more than 5 cycles, suggesting that some patients may benefit from prolonged chemotherapy and dinutuximab beta treatment. Fourteen of our 25 patients had previously received dinutuximab beta, four of whom achieved complete response and six partial response (objective response rate 71%). The therapy was well tolerated, even in heavily pre-treated patients and those who had previously received dinutuximab beta treatment. Toxicities were comparable to those previously reported for the individual therapies, and no discontinuations due to toxicities occurred. Combination of chemotherapy with dinutuximab beta is a promising treatment option for patients with relapsed or refractory high-risk neuroblastoma and should be further explored in clinical studies.